PENGARUH BIMBINGAN INTENSIF PENGARUH BIMBINGAN INTENSIF TERHADAP PENINGKATAN KELULUSAN UJI KOMPETENSI NERS INDONESIA - Rian Tasalim; Ardhia Redina Cahyani; Muhammad Malik Pajar (Universitas Muhammadiyah Banjarmasin, 2021)
ABSTRACT Background: Competency testing is an activity carried out to measure the competence of a nurse, to assess several aspects including knowledge, skills and professional behavior. The passing rate of the competency test in 2018 is 50.38%. These results are certainly still below the expected target to be achieved. Intensive guidance is an activity carried out by students of the nursing profession to gain insight into competency tests, such as learning and cases related to the Indonesian national competency test. It is hoped that the implementation of intensive guidance can increase the passing rate of the competency test for Indonesian nurses. Research Objectives: To identify the effect of intensive guidance on increasing the graduation of the Indonesian Nurse competency test. Research Methods: This type of research is a quantitative study with a pre-experimental research design using a Cross-Sectional Study approach. The number of samples in the study was 22 people, sampling using the total sampling technique. Data aids in research using an e-questionnaire. Statistical analysis using the Spearman rank test. Results: There is no relationship between improvement guidance and increasing graduation of the Indonesian Nurse competency test at Sari Mulia University with a significant value of P-Value = 0.701. Conclusion: Intensive guidance is not the main factor that can affect the passing rate, but there are many other factors that can affect the passing rate including following the competency test, academic achievement, intrinsic motivation, and the type of student learning.